Pa Jinglebob and the Grabble Gang - Arrigan, Mary; Paul, Korky (New York, NY Crabtree Pub. Co, 2005)
Although what Pa Jinglebob really likes to do is knit, as sheriff of Buckeroo and he must take action when the dastardly Mr. Grabble and his gang try to cheat residents out of their land to build a railroad straight through town
8 11
Keywords: Knitting -- Fiction; Sheriffs -- Fiction; Swindlers and swindling -- Fiction; West (U.S.) -- Fiction